Rapid synthesis of ultra-long silver nanowires for high performance transparent electrodes. Issue 9 (20th July 2020) - Madeira, Alexandra; Papanastasiou, Dorina T.; Toupance, Thierry; Servant, Laurent; Tréguer-Delapierre, Mona; Bellet, Daniel; Goldthorpe, I. A.
Abstract : Ultra-long silver nanowires are rapidly synthesized at low temperatures by using 1, 2-propanediol as the reaction solvent and lead to transparent electrodes with excellent optoelectronic properties. Abstract : By using 1, 2-propanediol instead of the classic polyol solvent, ethylene glycol, ultra-long silver nanowires are obtained in only 1 h. These nanowires lead to transparent electrodes with a sheet resistance of 5 Ohms per sq at a transparency of 94%, one of the highest figures of merit for nanowire electrodes ever reported.